The recruitment and retention of medical professionals in rural areas at the Limpopo Department of Health, South Africa - Nkgapele, Simon Matome (My University, 2025)
The shortage and retention of medical professionals is a serious international conundrum in the health sector. It remains a key issue in South Africa, impacting society's access to healthcare services, especially in rural areas. The demand for recruiting and retaining medical professionals to meet the health needs of South Africans is demonstrated by the National Development Plan (NDP): Vision for 2030. This points out the importance of recruiting and retaining medical professionals, as the sector depends on these professionals to deliver healthcare services to the community. Previous studies examined the conundrums of recruiting and retaining medical professionals across the health sector. However, they have not explicitly focused on the public health sector, including rural and urban hospitals. Less attention has been given to the rural areas of Limpopo province. In addition to the above, the available studies have not thoroughly examined the factors contributing to turnover. They also have not evaluated the effectiveness of incentive programs, support structures, and recruitment and retention strategies implemented by the Limpopo Department of Health (DoH) in rural public hospitals. Thus, this current research exists to examine the recruitment and retention of medical professionals in rural areas and suggest strategies for the Limpopo DoH to attract and retain these professionals effectively. This research employed a qualitative method of research. The research had semi-structured interviews and paper-based questionnaires. The findings were analysed using thematic content analysis. Thus, themes were identified and presented. The research found that the poor appeal of rural areas, caused by infrastructure deficits, social isolation, limited career growth, and misaligned recruitment, makes attracting and retaining professionals difficult. Medical professionals often leave rural posts due to poor conditions, high workloads, burnout, and better opportunities elsewhere. Generic incentive programs like allowances and overtime are only partially effective. The study calls for localised retention strategies, including decentralised recruitment, infrastructure improvement, permanent posts, career development, and better interdepartmental collaboration. The study recommends including rural-focused bursaries, enhancing living conditions, succession planning, and family-friendly workplaces to tackle systemic challenges and enhance healthcare in rural areas of the Limpopo province. These recommendations align with national priorities and constitutional obligations to ensure every South African has access to equitable and quality health services. The research contributes to public administration practices in public health and public sector Human Resource Management (HRM) and provides a theoretical contribution to the HRM sub-field in Public Administration.
Thesis (MPAM. (Public Administration)) -- University of Limpopo, 2025
Keywords: Recruitment; Retention; Rural areas; Turnover; Turnover; Medical professional; Employees -- Recruiting; Medical personnel; Medical personnel -- Recruiting; Rural hospitals